I gränslandet mellan aktiebolagsrätt och exekutionsrätt - En komparativ studie om röstbindningsavtal och möjligheten till verkställighet - Varadi Karlsson,Emilia (2024)
Shareholders’ agreements are a common contractual institution in Swedish and Norwegian company law and regulate the relationship between the share-holders of the limited company. A common form of shareholder agreement is the voting rights agreement, which aims to regulate the voting rights that shareholders receive because of holding shares in a limited company. The effect of a shareholders’ agreement is limited by the separation principle, which states that a shareholders’ agreement can never have legal effect with-out the support of law. In the spring of 2023, the legal situation in Norway changed in a fundamental way following a judgment of the Supreme Court. It is now possible to enforce obligations in a shareholders’ agreement by having the applicant shareholder, himself or through the Enforcement Authority, fulfill the voting obligation of the defaulting party at the general meeting (cf. HR-2023-782-U). Given the similarity of the countries’ legislation in this area, and the lack of a guiding judgment in Swedish law, this study aims to investigate the possibility of enforceability of voting agreements under Chapter 16, Section 12 of the Swedish Enforcement Code. In addition, the work aims to identify similarities and/or differences between the legal systems. The paper thus describes the shareholder agreement as a contractual figure, the meaning of voting agree-ments and the importance of the separation principle for shareholder agree-ments. The similarities identified are that the separation principle applies as a general rule in the legal systems, and that the meaning of a voting agreement appears to be the same. Moreover, there are similarities in the regulation of enforce-ment. One difference is that the issue of enforcement of shareholders’ agreements has been discussed in more detail in Norwegian doctrine, and authors have shown a more favorable attitude towards making exceptions to the separation principle. The Norwegian decision shows that the nature of the obligation is decisive for the question of whether enforcement can take place pursuant to the first paragraph of Section 13-14 of the Norwegian Enforcement Act. Since shareholders may entrust proxies with the exercise of their voting rights pursuant to Section 5-2 of the Norwegian Private Limited Liability Companies Act, such an obligation is not considered to be of a personal nature, and the voting rights may therefore be enforced by allowing the plaintiff to vote for the defendant’s shares. This provision corresponds to Chapter 7, Section 3 of the Swedish Companies Act. In conclusion, the study shows that, under Swedish Law, it appears possible to compulsorily enforce obligations in a voting agreement. Applying the Norwegian approach, it is possible to allow the applicant shareholder to exercise the voting rights of the party in dispute at the general meeting. The conclusion is justified by the fact that the first paragraph of Section 13-14 of the Norwegian Enforcement Act and Chapter 16, Section 12 of the Swedish Enforcement Code are similar as regards the three alternatives to enforcement.
Keywords: associationsrätt; aktieägaravtal